Addressing norm conflicts in a fragmented legal system : the doctrine of lex specialis - Lindroos, Anja (Nordic journal of international law, 2005)
Abstract (s. 27).
Keywords: kansainvälinen oikeus; säädöshierarkia; oikeusjärjestelmät; oikeuslähteet; laintulkinta; ihmisoikeudet; Euroopan ihmisoikeustuomioistuin